Molecular Evolutionary Analyses of the RNA-Dependent RNA Polymerase Region in Norovirus Genogroup II - Ozaki, Keita; Matsushima, Yuki; Nagasawa, Koo; Motoya, Takumi; Ryo, Akihide; Kuroda, Makoto; Katayama, Kazuhiko; Kimura, Hirokazu (Frontiers in Microbiology, 2018)
Noroviruses are the leading cause of viral gastroenteritis across the world in humans. RNA-dependent RNA polymerase (RdRp) plays a critical role in the replication of the viral genome. Although there have been some reports on a limited number of genotypes with respect to norovirus evolution of the RdRp region, no comprehensive molecular evolution examination of norovirus GII genotypes has yet been undertaken. Therefore, we conducted an evolutionary analysis of the 25 genotypes of the norovirus GII RdRp region (full-length) collected globally using different bioinformatics technologies. The time-scaled phylogenetic tree generated using the Bayesian Markov Chain Monte Carlo (MCMC) method indicated that the common ancestor of GII diverged from GIV around 1443 CE [95% highest posterior density (HPD), 1336–1542]. The GII RdRp region emerged around 1731 CE (95% HPD, 1703–1757), forming three lineages. The evolutionary rate of the RdRp region of norovirus GII strains was estimated at over 10−3 substitutions/site/year. The evolutionary rates were significantly distinct in each genotype. The composition of the phylogenetic distances differed among the strains for each genotype. Furthermore, we mapped the negative selection sites on the RdRp protein, and many of these were predicted in the GII.P4 RdRp proteins. The phylodynamics of GII.P4, GII.P12, GII.P16 and GII.Pe showed that their effective population sizes increased during the period from 2003 to 2014. Our results cumulatively suggest that the RdRp region of norovirus GII rapidly and uniquely evolved with a high divergence similar to that of norovirus VP1gene.